INHIBITIVE ENHANCEMENT OF ISONIASID TREATMENT ON MYCOBACTERIUM TUBERCULOSIS THROUGH TRITERPENOID CARBOCYLIC ACID FROM RED ALGAE EUCHEMA SPINOSUM - AHYAR AHMAD; MUH. NASRUM MASSI (International Journal of Pharma and Bio Sciences, 2013)
Anti-mycobacterial bioactivity of non polar compounds from red algae Euchema spinosum of Barang Lompo Island was studied. A triterpenoid carbocylic acid has been isolated from the chloroform fraction of Euchema spinosum, and its structure was determined by spectroscopic evidences including IR and 2D NMR and compared to previous data. The isolate was active against Mycobacterium tuberculosis at concentration 4 µg/mL, and could also increase the sensitivity of this pathogen to isoniasid drug. These studies suggest that anti-mycobacterial triterpenoid carbocylic acid in combination with isoniasid may play an important role in host defence against M. tuberculosis strain H37Rv.